The efficacy of the interleukin 17 inhibitor ixekizumab in psoriatic arthritis: data from real clinical practice - I. M. Marusenko; O. N. Sakovich (Современная ревматология)
The article describes the peculiarities of drug provision for patients with psoriatic arthritis (PsA) in the Republic of Karelia. We present a clinical case of effective treatment with interleukin 17 inhibitor ixekizumab (IXE) in a randomized clinical trial and real clinical practice in a patient with PsA. The distinctive feature of this case is the severity of PsA course that was not controlled by standard methods of therapy. IXE treatment was characterized by a rapid clinical improvement of both articular and skin symptoms and subsequent achievement of remission, which lasted for 3 years (on the therapy). The forced interruption of the treatment led to the relapse of the disease in a short amount of time. In 2 years IXE therapy was resumed; after 6 months of continuing treatment a stable remission of PsA was achieved. The patient is still in clinical remission (on therapy).